Core‐shell structured iron‐containing ceramic nanoparticles: Facile fabrication and excellent electromagnetic absorption properties. Issue 12 (12th June 2019) - Gu, Chong; Guo, Changqing; Dong, Xichao; Hu, Zhiming; Wu, Pengfei; Su, Zhiming; Lu, Yingxi; Xu, Binbin; Yu, Zhaoju; Liu, Anhua
Abstract: In this work, novel core‐shell structured Fe3 Si@C/SiC/Fe3 O4 /SiO2 nanoparticles were fabricated via a polymer‐derived ceramic approach, starting from sol‐like polycarbosilane‐encapsulated polynuclear carbonyl iron nanoparticles and with pitch as an isolator to avoid aggregation during polymer‐to‐ceramic transformation. Elemental analysis, X‐ray photoelectron spectroscopy, X‐ray diffraction, transmission electron microscope, vibrating sample magnetometer and vector network analyzer were employed to investigate the composition, nano/microstructure, morphology, and dielectric/magnetic properties. The results show that the size of obtained Fe3 Si@C/SiC/Fe3 O4 /SiO2 nanoparticles is in the range of 2‐200 nm. And the unique core‐shell structure with the hetero‐interface combined with simultaneous dielectric and magnetic loss endow Fe3 Si@C/SiC/Fe3 O4 /SiO2 nanoparticles outstanding electromagnetic (EM) wave absorbing performance. With a sample thickness of 4.5 mm, the minimum reflection coefficient (RC) of the composites Fe3 Si@C/SiC/Fe3 O4 /SiO2 mixed with paraffin wax reaches −44.7 dB, indicating that more than 99.99% EM waves can be attenuated by the composites. By adjusting the sample thicknesses, the effective bandwidth (the bandwidth of RC values lower than −10 dB) amounts 9.5 GHz (from 2.5 to 12.0 GHz), covering the whole C and X bands. Abstract : This is a unique study, where the fabrication and electromagnetic wave absorption performance of core‐shell structured Fe3 Si@C/SiC/Fe3 O4 /SiO2 nanoparticles were investigated.